2020
DOI: 10.1093/mnras/staa699
|View full text |Cite
|
Sign up to set email alerts
|

Secular changes in the orbits of the quadruple system VW LMi

Abstract: VW LMi is the tightest known quadruple system with 2+2 hierarchy. It consists of a W UMa-type eclipsing binary (P 12 = 0.47755 days) and another detached non-eclipsing binary (P 34 = 7.93 days) orbiting around a common center of mass in about P 1234 = 355 days. We present new observations of the system extending the time baseline to study long-term perturbations in the system and to improve orbital elements. The multi-dataset modeling of the system (4 radial-velocity curves for the components and the timing da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The most compact among known 2+2 quadruples is VW LMi (11029+3035, HD 95660) with an outer period of only 355 days [79]. The inner periods are 7.93 and 0.48 days.…”
Section: Compact Hierarchiesmentioning
confidence: 99%
“…The most compact among known 2+2 quadruples is VW LMi (11029+3035, HD 95660) with an outer period of only 355 days [79]. The inner periods are 7.93 and 0.48 days.…”
Section: Compact Hierarchiesmentioning
confidence: 99%
“…Therefore, we can conclude that, as was expected, the omission of the quadratic ETV term in the complex spectro-photodynamical analysis did not influence our basic solutions, but suggests that the 12 We emphasize that this holds only for doubly eclipsing 2+2 quadruples. The shortest period known 2+2 quadruple system, VW LMi has a much shorter outer period of Pout = 355 days (Pribulla et al 2008(Pribulla et al , 2020. Furthermore, in the case of the doubly eclipsing quadruple star EPIC 220204960 Rappaport et al (2017) reported that the outer period is very likely between 300 and 500 d, but an accurate value for that system is unknown.…”
Section: Orbital Configurationmentioning
confidence: 99%
“…The median period of the outer orbit was found to be P out = 858 +7 −5 d, with a moderate eccentricity of e out = 0.36 +0.02 −0.03 . (For comparison, note that the tightest known 2+2 quadruple system, VW LMi, has an outer period of P out = 355 d and eccentricity of e out < 0.1, see Pribulla et al 2008Pribulla et al , 2020 One should keep in mind, however, that while the bound quadruple nature of the system is certainly beyond question, the quantitative results on the orbital parameters of the outer orbit should be considered only with caution. The reason is, that the TESS observations cover only a fraction of an outer or-bital period and, furthermore, the four former, seasonal WASP minima have large uncertainties.…”
Section: Dynamical Properties Of the Quadruplementioning
confidence: 99%